The Relationship between Knowledge and Skills of Nurses and Triage Measures in the Emergency Room (Igd) of the Islam Malahayati Hospital in Medan in 2022 - Syamsul Idris (Science Midwifery, 2022)
Data on patient visits to the emergency room around the world has increased from year to year where 50% of them are visits with non-urgent conditions. In Indonesia, the data on patient visits to the ER is 4,402,205 patients (13.3%) of the total of all visits at the General Hospital, where this makes nurses have to sort out patients quickly and precisely according to priorities. To support this, knowledge and skills are needed to minimize the separation of types and emergencies of patients in triage, so that the treatment carried out is more optimal. The aim of the study was to determine the relationship between knowledge and skills of nurses and triage measures. Triage is a way to select or sort victims based on their level of emergency. This type of research is Correlation Researchwith a quantitative cross sectional research design. The population in this study were all nurses in the Emergency Room at the Malahayati Islamic Hospital in Medan. The sampling technique is saturated sample, with a total sample of 14 nurses. The instrument in this study was a questionnaire consisting of a questionnaire on nurses' knowledge about triage and nurse skills.The research instrument uses an observation sheet. Bivariate analysis with Chi square test. The research results show thatthere is a relationship between nurse knowledge and nurse skills with triage measures with a p-value coefficient of 0.03 <0.05, which means Ho is rejected and Ha is accepted. The conclusion is that there are 11 (78.6%) respondents who have a moderate level of knowledge with a ready skill level in the Emergency Room of the Islam Malahayati Hospital, Medan. From this study it is suggested that nurses always increase their knowledge, especially about triage.